3D Printing of Reduced Graphene Oxide Nanowires. (13th November 2014) - Kim, Jung Hyun; Chang, Won Suk; Kim, Daeho; Yang, Jong Ryul; Han, Joong Tark; Lee, Geon‐Woong; Kim, Ji Tae; Seol, Seung Kwon
<x xml:space="preserve">Abstract</x> 3D printing of reduced graphene oxide (rGO) nanowires is realized at room temperature by local growth of GO at the meniscus formed at a micropipette tip followed by reduction of GO by thermal or chemical treatment. 3D rGO nanowires with diverse and complicated forms are successfully printed, demonstrating their ability to grow in any direction and at the selected sites. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>